Promoting Mental Health and Preventing Mental Illness in General Practice. Issue 1 (2nd January 2016) - Thomas, Steve; Jenkins, Rachel; Burch, Tony; Calamos Nasir, Laura; Fisher, Brian; Giotaki, Gina; Gnani, Shamini; Hertel, Lise; Marks, Marina; Mathers, Nigel; Millington-Sanders, Catherine; Morris, David; et al.
Abstract: This paper calls for the routine integration of mental health promotion and prevention into UK General Practice in order to reduce the burden of mental and physical disorders and the ensuing pressure on General Practice. The proposals & the resulting document (https://ethicscharity.files.wordpress.com/2015/09/rcgp_keymsg_150925_v5.pdf ) arise from an expert 'Think Tank' convened by the London Journal of Primary Care, Educational Trust for Health Improvement through Cognitive Strategies (ETHICS Foundation) and the Royal College of General Practitioners. It makes 12 recommendations for General Practice: (1) Mental health promotion and prevention are too important to wait. (2) Work with your community to map risk factors, resources and assets. (3) Good health care, medicine and best practice are biopsychosocial rather than purely physical. (4) Integrate mental health promotion and prevention into your daily work. (5) Boost resilience in your community through approaches such as community development. (6) Identify people at increased risk of mental disorder for support and screening. (7) Support early intervention for people of all ages with signs of illness. (8) Maintain your biopsychosocial skills. (9) Ensure good communication, interdisciplinary team working and inter-sectoral working with other staff, teams and agencies. (10) Lead by example, taking action to promote the resilience of the general practice workforce. (11) Ensure mental health is appropriately included in the strategic agenda for your 'cluster' of General Practices, at the Clinical Commissioning Groups, and the Health and Wellbeing Board. (12) Be aware of national mental health strategies and localise them, including action to destigmatise mental illness within the context of community development.